PENDIDIKAN BUDAYA LOKAL DI MANGGARAI - Widyawati, Fransiska; Yohanes Servatius Lon (Unika Santu Paulus Ruteng, 2022)
The uniqueness of each culture is undoubtedly an asset to the nation. However, globalization has made strong global culture dominate and weaken the local cultures. This study is essential for maintaining and strengthening local cultures such as Manggaraian culture. It argues that 1) Cultural education is so natural to man that human nature can only be revealed through education and culture. 2) Local cultural education builds attitudes, knowledge, and skills so that students know and love their area's physical, social, cultural, and spiritual environment. 3) Local cultural education contributes very positively to the preservation and development of local wisdom, and it will be helpful for national development and global civilization. 4) Local cultural education must follow students' development and comprehensible competence and must be flexible in type, form, and arrangement. This study recommends the cooperation and involvement of parties such as the government, the educational institute, and the community to succeed in the local cultural education in Manggarai. It is especially recommended for the local government to provide legal, political, and financial support.